Embracing Their Prey at That Dark Hour: Common Cuttlefish (Sepia officinalis) Can Hunt in Nighttime Light Conditions - Brauckhoff, Melanie; Wahlberg, Magnus; Haga, Jens Ådne Rekkedal; Karlsen, Hans Erik; Wilson, Maria (Frontiers in Physiology, 2020)
Cuttlefish are highly efficient predators, which strongly rely on their anterior binocular visual field for hunting and prey capture. Their complex eyes possess adaptations for low light conditions. Recently, it was discovered that they display camouflaging behavior at night, perhaps to avoid detection by predators, or to increase their nighttime hunting success. This raises the question whether cuttlefish are capable of foraging during nighttime. In the present study, prey capture of the common cuttlefish (Sepia officinalis) was filmed with a high-speed video camera in different light conditions. Experiments were performed in daylight and with near-infrared light sources in two simulated nightlight conditions, as well as in darkness. The body of the common cuttlefish maintained a velocity of less than 0.1 m/s during prey capture, while the tentacles during the seizing phase reached velocities of up to 2.5 m/s and accelerations reached more than 420 m/s2 for single individuals. There was no significant difference between the day and nighttime trials, respectively. In complete darkness, the common cuttlefish was unable to catch any prey. Our results show that the common cuttlefish are capable of catching prey during day- and nighttime light conditions. The common cuttlefish employ similar sensory motor systems and prey capturing techniques during both day- and nighttime conditions.